Goodwill Impairment Test Disclosures under Uncertainty - Karol Marek Klimczak; Marta Dynel; Anna Pikos (Journal of Accounting and Management Information Systems (JAMIS), 2016)
The goal of this paper is to examine how disclosures of goodwill impairment tests under IAS 36 are prepared in conditions of high uncertainty. The data come from Polish companies listed at the Warsaw Stock Exchange, where economic and legal developments have been dynamic as compared to the main global equity markets, thus increasing uncertainty. We use interviews and content analysis, and we draw on genre theory to understand how narrative disclosures are written. We find that the disclosures follow clear rules of a genre, which require the financial statement disclosures to be a domain of facts. In cases where significant doubts concerning the reliability of impairment test outcomes exist, preparers place clues that professional readers can notice and follow to determine the reliability of test results themselves. These findings suggest that specific disclosure requirements are needed in countries where the national culture does not favor open discussions of the limitations to the reliability of accounting numbers.
Keywords: M41; 650; disclosure; narrative; content analysis; interview